Lesotho Poverty Reduction Strategy Paper Status Report (IMF Staff Country Reports, 2004)
This paper reviews Lesotho's Poverty Reduction Strategy Paper (PRSP) Status Report. The main activities undertaken between July 2003 and June 2004 included a costing exercise that analyzed all of the proposed activities under each PRSP strategy and compiled indicative cost estimates. An updated assessment of the aggregate resource envelope was done based on the medium-term fiscal strategy 2004/05-2006/07. A prioritization exercise was designed to identify core activities to be included in the PRSP on the basis of their expected contribution to the national development objectives